(untitled) (Global Journal of Management and Business Research, 2016)
The purpose of this study is to provide an insight into the impact of relationship marketing strategy on customer loyalty of retail bank sector in Pakistan and to examines whether these relationship strengthen through improvements in banking relationship. A questionnaire derived from previous studies and relevant literature was completed by 100 university students having accounts in different banks and Convenience sampling used. Multiple regression analysis assessed the impact on customer loyalty of four key construct of relationship marketing (Trust, Commitment, Communication and conflict handling). Results indicate that four variables have significant effect and predict good proportion of variance in customer loyalty.It is reasonable to conclude, on this evidence, that customer loyalty can be created, reinforced and retained by marketing plans aimed at building trust, demonstrating commitment to service, communicating with customers in a timely, reliable and proactive fashion, and handling conflict efficiently.